A Smart "Energy NanoLock" Selectively Blocks Oral Cancer Energy Metabolism through Synergistic Inhibition of Exogenous Nutrient Supply and Endogenous Energy Production. Issue 3 (16th December 2022) - Xu, Yurui; Zhang, Xiaomin; Zhou, Anwei; Cheng, Can; Chen, Kerong; Zhou, Xinyuan; Zhang, Gui; Ding, Likang; Wu, Xiaotong; Ge, Haixiong; Wu, Heming; Ning, Xinghai
Abstract: The major challenge in oral cancer is the lack of state‐of‐the‐art treatment modality that effectively cures cancer while preserving oral functions. Recent insights into tumor metabolic dependency provide a therapeutic opportunity for exploring optimal treatment approaches. Herein, a smart responsive "Energy NanoLock" is developed to improve cancer metabolic intervention by simultaneously inhibiting nutrient supply and energy production. NanoLock is a pomegranate‐like nanocomplex of cyclicRGD‐modified carboxymethyl chitosan (CyclicRC, pI = 6.7) encapsulating indocyanine green and apoptotic peptides functionalized gold nanoparticles (IK‐AuNPs), which together form a dual pH‐ and photoresponsive therapeutic platform. NanoLock exhibits good stability under physiological conditions, but releases small‐size CyclicRC and IK‐AuNPs in response to the tumor acidic microenvironment, leading to deep tumor penetration. CyclicRC targets integrins to inhibit tumor angiogenesis, and consequently blocks tumor nutrient supply. Meanwhile, IK‐AuNPs specifically induce apoptotic peptides and photothermally mediated mitochondrial collapse, and consequently inhibits endogenous energy production, thereby facilitating cell death. Importantly, in both xenograft and orthotopic oral cancer models, NanoLock selectively eliminates tumors with little cross‐reactivity with normal tissues, especially oral functions, resulting in prolonged survival of mice. Therefore, NanoLock provides a novel metabolic therapy to exploit synergistic inhibition of exogenous nutrient supply and endogenous energy production, which potentially advances oral cancer treatment. Abstract : A smart responsive "Energy NanoLock" is developed to improve oral cancer metabolic intervention. NanoLock is a pomegranate‐like nanocomplex of cyclicRGD‐modified carboxymethyl chitosan encapsulating indocyanine green and apoptotic peptides functionalized gold nanoparticles, which together form a dual pH‐ and photoresponsive therapeutic platform. NanoLock can simultaneously inhibit nutrient supply and energy production, resulting in effectively eliminating tumors while preserving oral functions.